Analisis Rasio Keuangan PT. Bank Central Asia Tbk - Shipa Nur Fadila; Nur Muhamad Fachrurrozi; Rangga Dimas Dimas; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study is to determine the liquidity ratio at PT. Bank Central Asia for the 2018–2022 period, the solvency ratio at PT. Bank Central Asia for the 2018–2022 period, and financial ratios at PT. Bank Central Asia based on analysis of liquidity and solvency ratios for the 2018–2022 period. The method of this research is a qualitative method. The results of this discussion are the analysis of financial ratios at Bank Central Asia Tbk in 2018–2022 which are summarized as follows. The conclusions reached are: Using the indicators Quick Ratio, Banking Ratio, Loan to Assets Ratio, and Loan to Deposit Ratio reveals financial conditions that tend to change from time to time, with the result that the amount of the loan given is less than the amount of cash deposited by depositor. Solvability ratio analysis conducted by Bank Central Asia Tbk for the 2018–2022 period shows that the Primary Ratio and Capital Adequacy Ratio indicators tend to decrease, making it difficult for banks to manage losses that occur during each period. It can be concluded from all the analyzes of the Liquidity Ratio and Solvency Ratio that have been carried out that the analysis of the financial performance of PT Bank Central Asia for the 2018-2022 period has experienced a significant increase Keywords: Liquidity, Solvency, Ratio